49=1-4(y-10)

Simple and best practice solution for 49=1-4(y-10) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 49=1-4(y-10) equation:



49=1-4(y-10)
We move all terms to the left:
49-(1-4(y-10))=0
We calculate terms in parentheses: -(1-4(y-10)), so:
1-4(y-10)
determiningTheFunctionDomain -4(y-10)+1
We multiply parentheses
-4y+40+1
We add all the numbers together, and all the variables
-4y+41
Back to the equation:
-(-4y+41)
We get rid of parentheses
4y-41+49=0
We add all the numbers together, and all the variables
4y+8=0
We move all terms containing y to the left, all other terms to the right
4y=-8
y=-8/4
y=-2

See similar equations:

| 3(y+4)-9(y-8)=114 | | x+(x-4)+(3x-9)=90 | | 4+9(p-10)=-84-(2-2p) | | 3(x+1)=8+x | | 18.00+1.50h=13.00+2.75h | | 8(y-4)-y=128-3(2+5y) | | 1/x=5/60 | | x+x-4+3x-9=90 | | 18+6(6-2y)=-6(y-8+6) | | .75x=57000 | | X+42°+2x+1°=180° | | 90x+120=100 | | 10m+41=-m^2 | | 3•(2x+10)=5•(x+11) | | p/2+14=11 | | -9y+5y=5-8y-21 | | k/4-6=-7 | | u/3+4=5 | | 4/z-z+2/2z=1 | | 6p+9=17+5 | | g/2+3=-1 | | 3+3a=9 | | t/5-5=-7 | | 6y+7=3y+5 | | x*x=112 | | 6a+7=39+5 | | 5(x+30)=7x+30 | | 10-4a=6a+60 | | -12x^2=34x+-28 | | -10a+4=-a-86 | | 2x-30=x+12 | | −10y+4=−y−86 |

Equations solver categories